Ménière’s Disease: Current Pharmacological and Surgical Approaches: A Review of Therapeutic Strategies - Kolenda, Dominika; Fischer, Zuzanna; Podolak, Marcin; Hładki, Michał; Simachi, Michalina; Janiszewska, Michalina; Imbirska, Beata; Prager-Zimny, Marta; Cyrulik, Michalina; Ramlau, Natalia (Journal of Education, Health and Sport, 2025)
Ménière’s disease (MD) is a chronic inner ear disorder characterised by recurrent vertigo episodes, fluctuating sensorineural hearing loss, tinnitus, and aural fullness, which may severely compromise quality of life. The etiopathogenesis of MD remains incompletely understood; however, the presence of endolymphatic hydrops is recognised as a central pathophysiological mechanism with additional contributions from autoimmune, infectious, genetic and microcirculatory factors . Consequently, therapeutic approaches are predominantly symptomatic, aiming to improve functional outcomes rather than provide a definitive cure. Current management includes pharmacological therapies, local (intratympanic) interventions and various surgical modalities. This review critically evaluates recent meta-analyses and systematic reviews with the goal of guiding evidence-based clinical decision-making and balancing therapeutic efficacy against potential adverse outcomes.